NMR-Based Μetabolomics of the Lipid Fraction of Organic and Conventional Bovine Milk - Tsiafoulis, Constantinos G.; Papaemmanouil, Christina; Alivertis, Dimitrios; Tzamaloukas, Ouranios; Miltiadou, Despoina; Balayssac, Stéphane; Malet-Martino, Myriam; Gerothanassis, Ioannis P. (My University, 2019)
Origin and quality identification in dairy products is an important issue and also an extremely challenging and complex experimental procedure. The objective of the present work was to compare the metabolite profile of the lipid fraction of organic and conventional bovine milk using NMR metabolomics analysis. ¹H-NMR and 1D TOCSY NMR methods of analysis were performed on extracted lipid fraction of lyophilized milk. For this purpose, 14 organic and 16 conventional retail milk samples were collected monthly, and 64 bulk-tank (58 conventional and 6 organics) milk samples were collected over a 14-month longitudinal study in Cyprus. Data were treated with multivariate methods (PCA, PLS-DA). Minor components were identified and quantified, and modification of the currently used equations is proposed. A significantly increased % content of conjugated (9-cis, 11-trans)18:2 linoleic acid (CLA), α-linolenic acid, linoleic acid, allylic protons and total unsaturated fatty acids (UFA) and decreased % content for caproleic acid were observed in the organic samples compared to the conventional ones. The present work confirms that lipid profile is affected by contrasting management system (organic vs. conventional), and supports the potential of NMR-based metabolomics for the rapid analysis and authentication of the milk from its lipid profile.
Keywords: Metabolic profile; NMR; Organic milk; CLA; UFA; 1D TOCSY